Narratives in/of Translations: A Trialogue on Translating Narratives Cross-Culturally - Brännlund, Emma; Kovacic, Tanja; Lounasmaa, Aura (Narrative Works, 2013)
Three authors, from different cultural contexts and research fields, engage in a trialogue, interrogating three stages of research—formulation of research protocol, field work, and data analysis—in order to explore some of the complexities of translating meaning across cultures. The voices merge into three conclusions regarding narratives in/of translation. First, narratives as translations are always in a process of being translated and re-constructed. Second, researchers have to be aware of power issues through the whole research process. Third, reflexivity needs to be incorporated in all stages of the research practice.